The Cambridge history of reformation-era theology - Appold, Kenneth G.; Minnich, Nelson H. (Cambridge University Press, 2024)
"The Cambridge History of Reformation-Era Theology explores the key developments in both Protestant and Catholic theology ca. 1475- 1650. Exploring the various settings and schools in which theology was formulated and taught, and the social backgrounds of its exponents-including women and non-university-trained men, as well as writers both in and outside Europe-it establishes how the major denominations took their positions and participated in a broader discourse. The volume examines specific theological themes from different denominational perspectives, demonstrating how theology affected the lives of believers via pastoral theology, canon law, and spirituality, and how theological ideas were linked to politics, warfare, science, and the arts. Written by an international team of leading scholars in the field, this History expands the range of theological discourse by introducing new topics and spokespersons, as well as global and ecumenical perspectives. It will remain the definitive place to begin any further study of theology during this period for years to come"--